2020
DOI: 10.1111/ejn.14681
|View full text |Cite
|
Sign up to set email alerts
|

A stable home‐base promotes allocentric memory representations of episodic‐like everyday spatial memory

Abstract: A key issue in neurobiological studies of episodic-like memory is the geometric frame of reference in which memory traces of experience are stored. Assumptions are sometimes made that specific protocols favour either allocentric (map-like) or egocentric (body-centred) representations. There are, however, grounds for suspect- K E Y W O R D Sevent arena, frames of reference, hippocampus, path integration, rats

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…In addition, we studied the within-and between-session strategies that mice employ in this task. Altering the start box location between and after encoding trials confirmed that mice primarily used an allocentric (world-centered) rather than egocentric (body-centered) reference frame (Figure S3A-D; 33 ). Within a session, mice focused their search progressively closer to the rewarded arm ( Figure S3E) and revisited non-rewarded arms less than expected from chance ( Figure S3F).…”
Section: Resultsmentioning
confidence: 83%
“…In addition, we studied the within-and between-session strategies that mice employ in this task. Altering the start box location between and after encoding trials confirmed that mice primarily used an allocentric (world-centered) rather than egocentric (body-centered) reference frame (Figure S3A-D; 33 ). Within a session, mice focused their search progressively closer to the rewarded arm ( Figure S3E) and revisited non-rewarded arms less than expected from chance ( Figure S3F).…”
Section: Resultsmentioning
confidence: 83%
“…Altering the start box location between and after ETs confirmed that mice primarily used an allocentric (world-centered) rather than egocentric (body-centered) reference frame (Figures S2A-S2D). 33 Within a session, mice revisited non-rewarded arms less than expected from chance (Figure S2E) and focused their search progressively closer to the rewarded arm (Figure S2F). Between sessions, the previous session's retrieval performance did not affect the next session's retrieval performance (Figure S2G), suggesting that a successfully stored memory did not interfere with learning of a new memory.…”
Section: Resultsmentioning
confidence: 97%
“…5 However, delayed memory stabilization was not observed in two earlier studies using the everyday memory task. 7,40 This variation can possibly be attributed to methodological differences such as the animal model, 7,40 number of ETs, 40 navigational strategy, 33 handling, or intertrial sleep epochs.…”
Section: Spaced Training Strengthens Memorymentioning
confidence: 99%
“…Initially, we established that our one-session learning paradigm in a Plusmaze led to long-term memory (24 h test) and was dependent on sleep. Plusmaze learning was performed in the event arena ( 11 13 ), with curtains included to limit the influence of uncontrolled room cues, but with large cues for spatial orientation placed on the curtain. Further, the walls of the event arena were inverted so that a cross-shaped maze was created covering 1.5 × 1.5 m with a track width of 15 cm.…”
Section: Resultsmentioning
confidence: 99%